A gene with major phenotypic effects as a target for selection vs. homogenizing gene flow. Issue 1 (28th November 2013) - Raeymaekers, Joost A. M.; Konijnendijk, Nellie; Larmuseau, Maarten H. D.; Hellemans, Bart; De, Luc; Volckaert, Filip A. M.
Abstract Genes with major phenotypic effects facilitate quantifying the contribution of genetic vs. plastic effects to adaptive divergence. A classical example is Ectodysplasin (Eda), the major gene controlling lateral plate phenotype in three‐spined stickleback. Completely plated marine stickleback populations evolved repeatedly towards low‐plated freshwater populations, representing a prime example of parallel evolution by natural selection. However, many populations remain polymorphic for lateral plate number. Possible explanations for this polymorphism include relaxation of selection, disruptive selection or a balance between divergent selection and gene flow. We investigated 15 polymorphic stickleback populations from brackish and freshwater habitats in coastal North‐western Europe. At each site, we tracked changes in allele frequency at the Eda gene between subadults in fall, adults in spring and juveniles in summer. Eda genotypes were also compared for body size and reproductive investment. We observed a fitness advantage for the Eda allele for the low morph in freshwater and for the allele for the complete morph in brackish water. Despite these results, the differentiation at the Eda gene was poorly correlated with habitat characteristics. Neutral population structure was the best predictor of spatial variation in lateral plate number, suggestive of a substantial effect of gene flow. A meta‐analysis revealed that the signature of selection at Eda was weak compared to similar studies in stickleback. We conclude that a balance between divergent selection and gene flow can maintain stickleback populations polymorphic for lateral plate number and that ecologically relevant genes may not always contribute much to local adaptation, even when targeted by selection.